Bond Markets in Africa - Mu, Yibin (IMF Working Papers; Working Paper ;, 2013)
African bond markets have been steadily growing in recent years, but nonetheless remain undeveloped. African countries would benefit from greater access to financing and deeper financial markets. This paper compiles a unique set of data on corporate bond markets in Africa. It then applies an econometric model to analyze the key determinants of African government securities market and corporate bond market capitalization. Government securities market capitalization is directly related to better institutions and interest rate volatility, and inversely related to the fiscal balance, higher interest rate spreads, exchange rate volatility, and current and capital account openness. Corporate bond market capitalization is directly linked to economic size, the level of development of the economy and financial markets, better institutions, and interest rate volatility, and inversely related to higher interest rate spreads and current account openness. Policy implications follow.